Effects of applying a multivariate training program on physical fitness and tactical performance in a team sport taught during physical education classes - Silva, Avelino; Ferraz, Ricardo; Branquinho, Luís; Dias, Tatiana; Teixeira, José E.; Marinho, Daniel A. (Frontiers in Sports and Active Living, 2023)
A multivariate training program could be a pedagogical choice to improve physical and tactical performance in a team sport taught during physical education classes at different levels of education. Thus, the aim of this study was to verify the effects of applying a multivariate training program on physical fitness and tactical performance during the teaching of a basketball didactic unit in basic and secondary education. Seventy-five students participated in the study. Seventy-five students from a Portuguese school (15.02 ± 1.31 years), among which forty-two students from primary school education and thirty-three students from secondary school. The FITescola® test battery was used to assess physical fitness (i.e., sit-ups, push-ups, horizontal impulse, shuttle test, 40m sprint, agility 4 x 10m). The Game Performance Assessment Instrument (GPAI) was used to assess students’ tactical performance for each player's game performance during a 20-minute 3 vs. 3 match. The GPAI variables were decision making index (DMI), skill execution index (SEI), support actions index (SI), and adaptability index (AI). During a basketball didactic unit teaching, the students were randomly divided into two groups, a control group that will not carry out the training program and an experimental group that will carry out a strength training program, high intensity explosive exercises and activities based on small-sided games (SSG) for 6 weeks. The two groups were evaluated in two moments: before the application of the training program and after the application of the training program regarding changes in physical fitness and tactical performance. The independent samples t-test (samples from two groups) and paired sample teste (for the same group) were applied for pre and post-assessment comparisons. All indexes present significant differences between primary and secondary students in the pre- and post-assessment tests with small effects (t = -6.54 to -4.82, ∆ = -27.57 to -0.16, p < 0.05 to < 0.001, d = 0.78 to 1.05). The results allow to conclude that in a school environment, a well-structured multivariate training program can effectively improve students' tactical skills, increasing their physical conditioning levels.